Low Voltage Capability of Generator for Frequency Regulation of Wind Energy System - Smrutiranjan Nayak; Sanjeeb kumar Kar; Subhransu Sekhar Dash (IAES Indonesian Section, 2021)
For the extraction of wind energy through a doubly fed induction generator (DFIG), low voltage is major particular essential controlled by the transmission structure executive. Under a structure issue condition, DFIG should remain with respect to the lattice for a particular least period and deal open power support on a case-by-case basis by the Transmission framework administrator. A pleasant control plot involving gear course of action through a superconducting resistance type issue current limiter (R-SFCL) and programming plan based on the rotor reference current direction control system (RRCOCS) with transient voltage control (TVC), is proposed in this paper to address the Low voltage essential. The results got by the proposed procedure are differentiated and RRCOCS and RRCOCS-TVC.